PARTY POLITICS AND ELECTIONS IN KOGI STATE BETWEEN 1999 AND 2015: A CASE STUDY OF THE PEOPLES DEMOCRATIC PARTY - ADAVIZE EMMANUEL JATTO; SUBERU OCHI ABDULRAHMAN (International Studies Journal, 2024)
Politics is a way of life and democracy has come to be seen as the world best practice in fair and equitable representation. This paper therefore tries to unravel the history, party politics and democracy in Kogi State especially in Nigeria’s Fourth Republic, the nature and history of the Peoples Democratic Party (PDP), one of the dominant political parties in the state in the period under review. Understanding the major political features of the state apparatus of the party is a big step in unraveling the dynamics of party politics in the state. In so doing, this paper deployed historical methodology and usedboth primary and secondary sources. This study examined the emergence of the Peoples Democratic party in the state as well as some major factors responsible for the success of the party in the 2003 elections and thereafter. It further highlighted some factors responsible for the defeat in the 2015 elections respectively. The paper argues that the major factor that influenced politics in Kogi state are ethnic issues or what is known as ethnic politics between the three major ethnic groups of Ebira, Igala and Okun. Intra-party squabbles and struggle for hegemony is also a factor among other factors. Findings in the paper reveal that these internal issues and personality clashes played a serious role in the party’s success and failure in elective positions within the state during the period under consideration. Thus, internal crisis, occasioned by personality clashes and ethnicity is a major factor that affects party politics in Kogi state.